KONTEMPORER FINISHING PADA MEDIA GERABAH NON SILIDRIS DENGAN TEKNIK PAINTING IN THE WATER - Arif Suharson; Dwita Anja Asmara (Institut Seni Indonesia Yogyakarta, 2013)
Creative terracotta products are required to meet the best possible standard ofmaterial, technique, and finishing method. Innovation in the shapes and finishing application ofnon-cylindrical terracotta products can be an appropriate solution to crease centre of interest,and to meet the need for contemporary and modern terracotta products in the market. Most ofthe artisans of terracotta products have not diversified their products. Neither have they madeinnovation about the design for non-cylindrical terracotta products for interior or exteriorornaments. The finishing of products has not improved due to the minimal knowledge in thecomposition of color and technique.This study is an applied research to identify the innovation in shapes of non-cylindricalterracotta products and the quality of terracotta art products. Finishing is the last step in theprocess of production. It has to be in harmony with the contemporary design and trend in orderto increase the price of products. This study specifically found the finishing composition withthe method of painting in the water the process of which is performed in the water to result inunique and artistic color combination.Products of the creative industry of terracotta have attracted both domestic andinternational consumers’ attention. Innovation in non-cylindrical shapes and application ofcontemporary finishing technique of painting in the water will be attractive and beneficial inimproving the quality of terracotta productions in global market era. Therefore, they can resultin superior advantages that lead to the increase of economic welfare especially for thoseinvolved in creative works of terracotta.Key words: finishing, terracotta, product, creative, technique Produk-produk kreatif seni gerabah terracotta dituntut mampu memenuhi standarkualitas baik dari segi, bahan, teknik, dan finishingnya. Inovasi bentuk gerabah non silindris danaplikasi finishing mampu menjadi solusi yang tepat untuk membuat centre of interest, danmengarah pada pemenuhan kebutuhan gerabah kontemporer atau modern, sehingga dapatmemenuhi keinginan pasar. Kalangan pengrajin banyak yang belum melakukan diversifikasidan inovasi desain bentuk gerabah non silindris yang difungsikan sebagai elemen seni hias interior/eksterior. Finishing produk gerabah juga mengalami kendala dan seolah hanya pasrahdengan finishing yang ada, dikarenakan minimnya pengetahuan dalam mengkomposisikanwarna dan teknik finishing baru yang dianggap sulit.Penelitian ini merupakan penelitian terapan yang mengarah pada inovasi bentukproduk gerabah non silindris dan pencapaian mutu finishing pada produk seni gerabahterracotta. Finishing merupakan teknik akhir dalam menyelesaikan produk agar menjadi lebihbaik, menyelaraskan dengan trend desain terkini, dan mampu mengangkat harga jual suatuproduk. Penelitian ini akan menemukan komposisi finishing dengan metode painting in thewater. Dimana proses pelaksanaan finishing gerabah dilakukan dalam air dengan hasil finishingkontemporer dengan perpaduan warna yang unik dan artistik.Produk-produk dari dunia industri kreatif terutama seni gerabah terracotta mulaibanyak diminati oleh konsumen, baik dari dalam negeri maupun luar negeri. Inovasi bentukgerabah non silindris dan aplikasi finishing kontemporer dengan teknik painting in the waterakan menjadi salah satu daya tarik dan mampu meningkatkan mutu produksi seni gerabahterracotta yang akan memberikan dampak kemajuan pada seni tradisional di era pasar global.Sehingga mampu memberikan keunggulan yang berdampak pada penghasilan ekonomikesejahteraan, terutama bagi insan dunia kreatif pada bidang seni gerabah terracota. Kata kunci: finishing, gerabah terracotta, produk, kreatif, teknik